Система екологічного моніторингу та управління природно-заповідного фонду Західного Полісся - Трофимчук, О.М.; Мокрий, В.І. (Екологічна безпека та природокористування, 2012)
Scientifically reasonable conception of the expertly-informative system of the ecological monitoring of the naturally-protected fund of Western Polesye, that has hierarchical character, containing conceptual principles of monitoring of forest on different levels, water, ground and antropogenics ecosystems, with co-ordination of measuring and integration of results through a research and information center.